Immune dysregulation due to bi-allelic mutation of the actin remodeling protein DIAPH1 - Bhattad, Sagar; Ramakrishna, Somashekara H.; Kumar, Ratan; Choi, Joseph M.; Markle, Janet G. (Frontiers in Immunology, 2024)
Children with severe inflammatory diseases are challenging to diagnose and treat, and the etiology of disease often remains unexplained. Here we present DIAPH1 deficiency as an unexpected genetic finding in a child with fatal inflammatory bowel disease who also displayed complex neurological and developmental phenotypes. Bi-allelic mutations of DIAPH1 were first described in patients with a severe neurological phenotype including microcephaly, intellectual disability, seizures, and blindness. Recent findings have expanded the clinical phenotype of DIAPH1 deficiency to include severe susceptibility to infections, placing this monogenic disease amongst the etiologies of inborn errors of immunity. Immune phenotypes in DIAPH1 deficiency are largely driven aberrant lymphocyte activation, particularly the failure to form an effective immune synapse in T cells. We present the case of a child with a novel homozygous deletion in DIAPH1, leading to a premature truncation in the Lasso domain of the protein. Unlike other cases of DIAPH1 deficiency, this patient did not have seizures or lung infections. Her major immune-related clinical symptoms were inflammation and enteropathy, diarrhea and failure to thrive. This patient did not show T or B cell lymphopenia but did have dramatically reduced naïve CD4+ and CD8+ T cells, expanded CD4-CD8-T cells, and elevated IgE. Similar to other cases of DIAPH1 deficiency, this patient had nonhematological phenotypes including microcephaly, developmental delay, and impaired vision. This patient's symptoms of immune dysregulation were not successfully controlled and were ultimately fatal. This case expands the clinical spectrum of DIAPH1 deficiency and reveals that autoimmune or inflammatory enteropathy may be the most prominent immunological manifestation of disease.